Minocycline-induced antineutrophil cytoplasmic antibody-associated vasculitis in children - Sunil Kapur; Jitendra Oswal (Indian Journal of Rheumatology)
Chronic exposure to minocycline, a commonly used anti-acne medication, results in a variety of autoimmune syndromes. Minocycline-induced vasculitis often associated with the presence of antinuclear antibody (ANA) and antineutrophil cytoplasmic antibody (ANCA) has been reported in Western literature, mainly in adults. Herein, we report a rare case of a 15-year-old male child on minocycline treatment for 1 year, who presented with fever, skin rash, and polyarthralgia for 4 months. His erythrocyte sedimentation rate (ESR) level was elevated, ANA and myeloperoxidase ANCA were positive, and skin biopsy revealed leukocytoclastic vasculitis. Upon discontinuation of minocycline and prescribing a short course of oral steroids, all his symptoms resolved and ESR normalized within 2 weeks. The child remained asymptomatic with normal acute-phase reactants at 2-month follow-up. This outcome suggested that minocycline was the main cause of ANCA-associated vasculitis.